Pretreatment 18F-fluorodeoxyglucose Uptake in the Lung Parenchyma Predicts Poor Survival After Stereotactic Body Radiation Therapy in Patients With Stage I Non-Small Cell Lung Cancer. (14th September 2018) - Satoh, Yoko; Motosugi, Utaroh; Saito, Akitoshi; Omiya, Yoshie; Onishi, Hiroshi
Purpose: In this study, we aimed to evaluate the prognostic value of fluorodeoxyglucose uptake in the lung parenchyma and the presence of subclinical interstitial lung disease on computed tomography as predictive factors for survival following stereotactic body radiation therapy in patients with stage I non-small cell lung cancer. Methods: We retrospectively evaluated 125 patients with stage I non-small cell lung cancer who underwent stereotactic body radiation therapy at our institute between December 2005 and March 2013 for various demographic and clinical parameters. The fluorodeoxyglucose uptake in the lung parenchyma corrected with computed tomography value (tissue fraction-corrected standardized uptake value) was quantified using fluorodeoxyglucose-positron emission tomography/computed tomography before the therapy. Additionally, the radiological findings of interstitial lung disease on computed tomography were evaluated. The prognostic analyses were performed using the Kaplan-Meier analysis and Cox proportional hazards regression model for univariate and multivariate analyses. Results: The median follow-up period was 39 months. The 3-year overall survival rate was 67.9%, and the 3-year progression-free survival rate was 52.0%. The multivariate analysis indicated that the tissue fraction-corrected standardized uptake value was correlated with the patients' overall survival ( P = .027, hazard ratio: 2.694, 95% confidence interval: 1.109-8.057). The presence of subclinical interstitial lung disease showed no correlation with the overall survival ( P = .535, hazard ratio: 1.256, 95% confidence interval: 0.592-2.473). Conclusion: The results indicated that fluorodeoxyglucose uptake in the lung parenchyma, expressed as the tissue fraction-corrected standardized uptake value, was an independent prognostic factor in patients with stage I non-small cell lung cancer who have received stereotactic body radiation therapy.